ANALISIS RESPON PENAWARAN DAN PERMINTAAN KARET ALAM INDONESIA - Agrippina Sinclair Sinclair; Djaimi Bakce; Jum’atri Yusri (Indonesian Journal of Agricultural Economics, 2015)
Indonesia is second largest country producer of natural rubber, and widest land in the world. Considerations in development of these commodity can be seen from response of supply and demand on various factors. This study aims to analyze supply and demand response of Indonesia natural rubber. Therefore, this study develop simultaneous equations model with Two Stage Least Square method. This study indicate predetermined variables which significantly respect to supply and demand Indonesia natural rubber are domestic natural rubber price, ratio of domestic natural rubber price and synthetic rubber price, and lag variable of Indonesia natural rubber production, demand, price, and export. There are no predetermined variables which responsive respect to Indonesia natural rubber supply and demand. However predetermined variables have large response to supply and demand; i.e. price of Indonesia natural rubber and synthetic rubber price in the world. This study recommended to Indonesia government to hold of higher Indonesia natural rubber price by increasing of Indonesia natural rubber quality products, and to develop downstream rubber industry seriously.